Elevated levels of the angiogenic cytokines basic fibroblast growth factor and vascular endothelial growth factor in sera of cancer patients. - Dirix, L. Y. (Nature Publishing Group, 1997)
The concentration of basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) was determined in the serum of 90 untreated and 42 treated metastatic cancer patients, including patients with colorectal, breast, ovarian and renal carcinomas, with an enzyme-linked immunosorbent assay (ELISA). Levels higher than the 95th percentile of the concentrations of a control group, i.e. 7.5 pg ml(-1) for bFGF and 500 pg ml(-1) for VEGF, were identified as 'elevated'. One measurement during follow-up was included into the analysis per patient. For 19 treated patients, consecutive serum samples were analysed. Fifty-seven per cent of all untreated patients had elevated serum levels of one or both angiogenic factors. The fraction of patients with elevated serum levels of bFGF and/or VEGF was similar in the different tumour types. Agreement of bFGF levels and VEGF levels, classified in relation to their respective cut-off values, was present in 67% of all patients. Fifty-eight per cent of the patients with progressive disease during treatment compared with 15% of the patients showing response to treatment (chi-squared test P < 0.05) had elevated bFGF and/or VEGF serum levels. When consecutive serum samples were analysed, two-thirds of the patients showing progressive disease had increasing serum levels of the angiogenic factors compared with less than one-tenth of the patients showing response (chi-squared test P < 0.05). The lack of association between the serum bFGF and VEGF levels and the tumour type may suggest an aspecific host reaction responsible for solid tumour-related angiogenesis. The main determinants of the serum bFGF and VEGF concentration are the progression kinetics of the metastatic carcinomas.